Laboratorios de informática para mejorar el proceso de cumplimiento fiscal de Colombia - González-Robayo, Fabián Giovanni; González-Sanabria, Juan Sebastián; Téllez-Hernández, Lucero (Revista Científica, 2019)
The paper proposes the use of a digital forensic laboratory to help solve the problem of tax evasion in Colombia that involves problems in covering the public obligations of the State, and leads people to have problems of consumption and savings that affect the economic dynamics, but beyond the normative implications it is observed that when implementing new technologies in the fiscal process to avoid or detect evasion, more efficient results are obtained. The computer process that helps cover tax evasion can be improved through digital analysis as reflected in the findings of evidence of the use of forensic laboratories.